Construction of superhydrophilic/underwater superoleophobic polydopamine‐modified h‐BN/poly(arylene ether nitrile) composite membrane for stable oil‐water emulsions separation. (20th January 2020) - Zhang, Guiyuan; Zhan, Yingqing; He, Shuangjiang; Zhang, Lianhong; Zeng, Guangyong; Chiao, Yu‐Hsuan
Abstract : Oil/water emulsion separation in harsh environments remains a big challenge. Herein, a double layered nanofibrous composite membrane was developed by assembly of polydopamine‐modified hexagonal boron nitride (h‐BN‐PDA) onto a poly(arylene ether nitrile) (PEN) nanofibrous mat. Owing to the synergistic effect of a h‐BN‐PDA skin layer and a PEN nanofibrous mat supporting layer, as‐prepared composite membrane exhibited high thermal stability, corrosion resistance, and superhydrophilic/underwater superoleophobic property. Consequently, the PEN composite membrane showed good antifouling performance and a high rejection ratio (>99.0%) for various oil/water emulsions. After 10 cycles, the separation flux of PEN composite membrane still reached 588.1 L/m 2  h under the operating pressure of 0.04 MPa. Furthermore, the PEN composite membrane could still achieve high separation efficiency and high flux in high‐temperature (65 °C) and strongly corrosive conditions (pH = 1‐13). Therefore, the stable and efficient h‐BN‐PDA/PEN composite membrane showed potential application for treating oily wastewater in harsh environments.